Efecto del tratamiento con ácido zoledrónico e hidroxocobalamina sobre la microarquitectura ósea en ratones con periodontitis y osteoporosis inducida: Estudio preclínico - Petkova-Gueorguieva, Marieta (2023)
Objective. Evaluate the effect of zoledronic acid and hydroxocobalamin treatment on alveolar bone microarchitecture in mice with induced periodontitis and osteoporosis. Methods. Experimental design in preclinical phase. Sixteen female mice were included in which osteoporosis was induced by total ovariectomy and periodontitis was also induced by inflammation by 5/0 black silk ligation of the maxillary second molar, all protocols were performed under general anesthesia. The mice were distributed into 4 groups: control, treatment with zoledronic acid, treatment with hydroxocobalamin and combined treatment. At 16 weeks, euthanasia was performed, dissection was performed for evaluation by microtomography; determining bone mineral density (BMD), bone volume (BV/TV), trabecular thickness (Tb.Th), number of trabeculae (Tb.N), trabecular separation (Tb.Sp); descriptive and bivariate analysis was performed using 1-way ANOVA with a 95% confidence level. Results. The group that received combined treatment of zoledronic acid and hydroxocobalamin presented higher bone mineral density (BMD), higher bone volume (BV/TV) and lower trabecular separation (Tb.Sp) compared to the control group (p<0.05). Conclusions. Combined treatment with zoledronic acid and hydroxocobalamin improves bone microarchitectural features in mice with induced osteoporosis and periodontitis.